Mixed convection in partially cooled lid-driven cavity filled with a non-Darcy porous medium - Öztop, Hakan Fehmi; Varol, Yasin; Pop, Ioan; Al-Saleem, Khaled (Inderscience Enterprises Ltd, 2012)
The effects of buoyancy-aiding or buoyancy-opposing mechanisms on laminar mixed convection heat transfer in a porous enclosure partially cooled from the left vertical wall has been analysed numerically for two different forms of thermal boundary conditions in steady-state regime using the Darcy-Brinkman-Forchheimer equation model. In the first case, top wall of the cavity moves from left to right (buoyancy-aiding) with constant speed but in the second case bottom wall moves in the same direction (buoyancy-opposing). In both cases, sliding wall has higher temperature than that of half of the left wall while remaining walls are insulated. Finite-volume-based finite difference method with Simple algorithm was applied to solve the governing equations. The Richardson number, Ri, in the range 0.05 <= Ri <= 10, Darcy number Da = 0.1, 0.01 and 0.001, and porosity 0.2 <= epsilon <= 0.6 are chosen as values of the dimensionless governing parameters. It is found that when bottom wall moves, an opposing mechanism is formed. Higher Nusselt numbers are obtained than that of aiding mechanism (moving top wall) for all values of the Darcy numbers.
Keywords: lid-driven cavity; non-Darcy porous medium; numerical solution